2018
DOI: 10.1186/s40359-018-0236-1
|View full text |Cite
|
Sign up to set email alerts
|

Memory-related subjective cognitive symptoms in the adult population: prevalence and associated factors – results of the LIFE-Adult-Study

Abstract: BackgroundSubjectively perceived memory problems (memory-related Subjective Cognitive Symptoms/SCS) can be an indicator of a pre-prodromal or prodromal stage of a neurodegenerative disease such as Alzheimer’s disease. We therefore sought to provide detailed empirical information on memory-related SCS in the dementia-free adult population including information on prevalence rates, associated factors and others.MethodsWe studied 8834 participants (40–79 years) of the population-based LIFE-Adult-Study. Weighted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
1
31
0
1
Order By: Relevance
“…Investigating memory decline in terms of self-reported problems or complaints can be beneficial for practise. Older adults are often discouraged seeking help for memory complaints by comparison to their peers or beliefs about the severity of their complaints (Hurt et al, 2012;Luck et al, 2018). From a health promotion perspective, people may be more likely to identify with 'memory problems' than seek treatment for dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating memory decline in terms of self-reported problems or complaints can be beneficial for practise. Older adults are often discouraged seeking help for memory complaints by comparison to their peers or beliefs about the severity of their complaints (Hurt et al, 2012;Luck et al, 2018). From a health promotion perspective, people may be more likely to identify with 'memory problems' than seek treatment for dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with memory complaints engage in low rates of help-seeking, in-part attributed to perceptions of their memory issues compared to their peers and the belief their issues don't require treatment (Hurt, Burns, Brown & Barrowclough, 2012). A population-based study of adults aged 40-79 years in Germany reported that one fifth of participants have or wanted to consult a professional about their memory problems (Luck et al, 2018). Health professionals will be the point of contact for older adults with memory complaints.…”
Section: Introductionmentioning
confidence: 99%
“…The prolonged, subjective symptoms frequently reported in the context of Lyme disease (e.g., fatigue, widespread pain, cognitive complaints, paresthesia, and sleep disruption) also broadly represent those commonly reported in outpatient settings (72)(73)(74). Furthermore, while some differences in impairment and symptom distribution have been studied and reported (75)(76)(77), there is also a degree of general symptom overlap with other disease states such as traumatic brain injury, depression, chronic fatigue syndrome, and fibromyalgia (78).…”
Section: Symptomsmentioning
confidence: 99%
“…The same holds for depression. The German population-based Leila75 + study showed a prevalence of depression in the 75 + year olds of 38.2% [43], the LIFE study with participants of the age from 18-80 a prevalence of 6.4 % [44]. In our cohort, we assessed prevalence (11.4%) using a cutoff of 2 or more points on one item of the PHQ-2; this potentially even overestimates the true prevalence of depression in our cohort.…”
Section: Discussionmentioning
confidence: 92%